Recycling of precious materials by modified electrospun membranes - AKTAŞ, SERDAR (DESALINATION PUBL, 2021)
In this study, adsorption of gold (Au) and platinum (Pt) ions by electrospun polyacrylonitrile (PAN) natural keratin- modified membranes with high sulfur content and affinity toward precious metals were investigated. Different adsorption parameters, sorbent amount, contact time, temperature and pH of solution on adsorption (%) were studied in detail in batch sorption. First, a PAN nanofiber membrane was fabricated by an electrospinning technique as a low-cost method for producing nanofiber membranes and was then modified with the natural keratin (human hair) by hydrolysis in a basic solution. A PAN-keratin nanofiber membrane was characterized by Fourier-transform infrared spectroscopy and scanning electron microscopy (FTIR and SEM, respectively). FTIR verified the modification of PAN with keratin in which the spectrum of the resulting membrane showed significant changes, by using this modified nanofiber membrane, Au adsorption of 99% was achieved while the Pt adsorption showed a maximum of 37%. The reason for this finding may be because the electronegativity of Au is higher than Pt. When the adsorption isotherms were investigated, it was noted that the Langmuir isotherm fit better than the Freundlich isotherm. 1.0 M thiourea solution was used as a desorption reagent for both Au and Pt ions. Reusability studies showed that the adsorption capacity can remain up to 90 % after four times of usage. This finding indicates that the adsorption process of precious ions onto the electrospun membrane is a monolayer adsorption process.
Keywords: Electrospinning; Adsorption; Gold; Platinum; Nanofiber membrane; Keratin; ADSORPTION; IONS; PLATINUM; OPTIMIZATION; CATALYSTS; RECOVERY; CHITOSAN; REMOVAL; WOOL